Proportion of Adults Meeting the 2018 Physical Activity Guidelines for Americans According to Accelerometers - Zachary Zenko; Erik A. Willis; David A. White; David A. White (Frontiers Media S.A., 2019)
The new 2018 Physical Activity Guidelines for Americans provides updated recommendations for physical activity behavior. These guidelines remove the requirement for physical activity to be obtained in bouts of at least 10 min. The purpose of the present study was to provide an updated estimate of the proportion of adults meeting the physical activity guidelines, based on nationally representative data using accelerometers. Data from 6,525 adults were included in this study. The proportion of adults meeting the physical activity guidelines according to the Department of Health and Human Services and according to the American College of Sports Medicine were estimated using (a) lifestyle activities and (b) ambulatory activities only. Estimates of the proportion of adults meeting the physical activity guidelines ranged from 3.4 to 95.6%, even when based on the same data. The large range of these estimates suggest that challenges exist when using accelerometer data to estimate the levels of physical activity behavior in the population. Further, the large range indicates that, perhaps, physical activity guidelines should not be used as a reference point for behavior change. Instead, we suggest that efforts should be made to promote physical activity in reference to current behavior.